The Efficacy of English Phonics Instruction in Helping EFL Students to Decode Vowel Digraph Letters - Putra, Rizky Anugrah (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2023)
The current study aimed to disclose how effective Phonics instruction is in increasing speech accuracy and glimpsing at students' perspectives on phonics learning in the classroom. This study applied quasi-experimental research involving 30 Department of Literature students learning English as a foreign language. The researcher also used the questionnaire to glimpse their perspective on phonics instruction. This study discovered that phonics learning significantly improved pronunciation accuracy and the ability to decode vowel digraph <ai>. In addition, students also have a positive view of phonics learning, which is one of the important materials at the beginning of the introduction of foreign language systems which helps them produce accurate utterances and helps improve literacy. The current study considers that phonics instruction needs to get important attention to become a solution to student learning problems.